Development and psychometric properties of the sound preference and hearing habits questionnaire (SP-HHQ). (25th May 2018) - Meis, Markus; Huber, Rainer; Fischer, Rosa-Linde; Schulte, Michael; Spilski, Jan; Meister, Hartmut
Abstract: Objective : The aim of the study was, based on the individualisation of hearing aids (HA) and pre-sets for audio devices, to develop a questionnaire to determine the basis for profiling sound preferences and hearing habits to gather additional information usable for HA fitting and adjustment tools for audio-devices. Methods : We developed a questionnaire consisting of 46 items. A postal survey was conducted with N = 622 users with a mean age of 66 years (47.9% aided with HA, 45.7% female). Results : Seven factors were identified by means of Explanatory and Confirmatory Factor Analyses: F1: 'Annoyance/distraction by background noise', F2: 'Importance of sound quality', F3: 'Noise Sensitivity', F4: 'Avoidance of unpredictable sounds', F5: 'Openness towards loud/new sounds', F6: 'Preferences for warm sounds', and F7: 'Details of environmental sounds/music'. Only the first of these factors was related to the audiogram of the user. No difference with any of the factors could be observed with HA use/non-use. In contrast, gender effects were found with female respondents preferring warm sounds and being more sensitive to noise. Conclusions : The sound preference and hearing habits questionnaire (SP-HHQ) is a usable tool for profiling the users with respect to sound preferences relevant for HA fitting and pre-sets for audio devices.